Surviving Personal Financial Strain Amid Covid-19 Outbreak: A Conceptual Review of South African Context: Array - Mbukanma, Ifeanyi; Ravinder, Rena; Ifeanyichukwu, Lydia Ugochi (Acta Universitatis Danubius. Œconomica, 2020)
The current outbreak of COVID-19 infection in Wuhan (China) and its spread around the globe has generated a huge panic on personal financial well-being, as most individuals face various financial difficulties to deal with tight government regulation of stay at home. Perhaps, achieving sound financial control will be the light at the end of the tunnel for someone seeking to bring their financial life in order in a lockdown situation. As the infection rate of Covid-19 rises in South Africa, this study reveals specific financial survival strategies that may cushion the financial control and management capabilities of South Africans. This objective, however, was achieved by conceptualizing the principles of personal financial control that fits the South African context, whose population are exposed to a credit system of the economy. Latest research on the update of Covid-19 infection, as well as findings in the area of personal financial control and management, was also reviewed to uncover personal financial survival strategies in the midst of the Covid-19 pandemic. Hence, the findings of this study provide an impetus to recommend that the knowledge of personal financial control strategies such as financial literacy, personal financial discipline and social external variables are needed by South Africans to survive the personal financial strain caused by Covid-19 outbreak.